Annexin A10 is involved in the development and maintenance of neuropathic pain in mice. (19th September 2016) - Lu, Ying; Ni, Sujie; He, Li-Na; Gao, Yong-Jing; Jiang, Bao-Chun
Highlights: Anxa10 was the most obviously upregulated annexin gene in the spinal cord in SNL mice compared with sham-operated mice. ANXA10 was persistently increased in both astrocytes and neurons in the superficial dorsal horn of the spinal cord after SNL. Stable suppression of Anxa10 gene expression by RNAi partially prevented and attenuated SNL-induced neuropathic pain. Abstract: ANXA10 (annexin A10) is a member of the annexin family, and its biological effects are mediated primarily through the calcium-dependent phospholipid-binding and calcium ion binding. We examined the gene expressions of the L5 spinal cord after spinal nerve ligation (SNL)-induced neuropathic pain in mice by gene chip. The results showed that Anxa10 mRNA was the most upregulated gene in annexin family with 73.7-fold increase. Although previous studies have reported that several annexins are involved in nociceptive pain, the role of Anxa10 in pain remains undefined. We aimed to evaluate the role of ANXA10 in mediating injury-induced heat hyperalgesia and mechanical allodynia. We found that SNL induced persistent upregulation of Anxa10 mRNA and protein in the spinal cord of mice. Moreover, ANXA10 was colocalized with the neuronal marker MAP2 and astrocytic marker glial fibrillary acidic protein (GFAP), but not with microglial marker CD11b. Finally, pretreatment with Anxa10 siRNA partially prevented SNL-induced mechanical allodynia and heat hyperalgesia. Posttreatment with Anxa10 siRNA attenuated SNL-induced neuropathic pain. These findings suggest that ANXA10 might be a novel target in the treatment of neuropathic pain.